Impact of artificially matured organic matter on the dielectric and elastic properties of compacted shales. Issue 1 (1st December 2018) - Cauchefert, Matthieu; Josh, Matthew; Esteban, Lionel; Vialle, Stephanie; Lebedev, Maxim; Dautriat, Jeremie; Sarout, Joel; Maney, Bruce
Abstract : Unconventional gas shale resources recently became a standard in the American oil and gas industry and are studied throughout the world. However, gas shales are still poorly characterised with respect to other reservoir rock types. The different parameters of organic matter (OM) in organic shales needs to be better constrained in all theircomplexity and variability. This study focuses on the influence of OM maturity on the dielectric and elastic response of shale using a hydrous pyrolysis process to increase their maturity. We then incorporated the OM in a shale-like mineral matrix that was artificially compacted under control. Elastic properties and their anisotropy were measured during compaction while dielectric measurements were acquired post-compaction. The results showed that OM affects the onset of the liquid/plastic transition of compacting sediment. The immature OM lessens the development of P-wave anisotropy. On the other end, mature OM strongly decreases the imaginary dielectric permittivity at low frequencies while it increases electrical conductivity.